2017
DOI: 10.1176/appi.ps.201600384
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk Assessment and Prevention: A Systematic Review Focusing on Veterans

Abstract: Risk assessment methods have been shown to be sensitive predictors of suicide and suicide attempts, but the frequency of false positives limits their clinical utility. Research to refine these methods and examine clinical applications is needed. Studies of suicide prevention interventions are inconclusive; trials of population-level interventions and promising therapies are required to support their clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 74 publications
1
32
2
Order By: Relevance
“…The mixed results from these primary studies are in line with the results of the reviews included in our rapid overview, as well as reviews conducted in other populations experiencing OSI. Two reviews examining mind and body therapy in military veterans showed improvement in PTSD symptoms and overall health of the participants [78,79], while a recent review of suicide prevention interventions in veterans found inconclusive results leading the study authors to recommend additional exploration using refined methods [80]. The similarity across populations further highlights the need for robust studies to better serve those impacted by OSI.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…The mixed results from these primary studies are in line with the results of the reviews included in our rapid overview, as well as reviews conducted in other populations experiencing OSI. Two reviews examining mind and body therapy in military veterans showed improvement in PTSD symptoms and overall health of the participants [78,79], while a recent review of suicide prevention interventions in veterans found inconclusive results leading the study authors to recommend additional exploration using refined methods [80]. The similarity across populations further highlights the need for robust studies to better serve those impacted by OSI.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Cancer October 15, 2018 in 55 cancer centers indicated that less than two-thirds of patients were screened. 57 Furthermore, many physicians may not be comfortable discussing psychosocial issues like suicide with patients or their relatives. 57 Furthermore, many physicians may not be comfortable discussing psychosocial issues like suicide with patients or their relatives.…”
Section: Clinical and Public Health Implicationsmentioning
confidence: 99%
“…52,54,55 The psychosocial literature indicates that screening for psychological distress may be inadequate, 56 and it is particularly difficult to screen for a low-incidence outcome like suicide. 57 Furthermore, many physicians may not be comfortable discussing psychosocial issues like suicide with patients or their relatives. 58 Therefore, although there is a growing consensus around the importance of appropriate assessment and follow-up after a positive distress screen, 59,60 assessing risk for suicide will likely require more time than is available in a routine office visit.…”
Section: Clinical and Public Health Implicationsmentioning
confidence: 99%
“…The positive predictive value of their model is 6%, which means that 17 individuals would need to receive an intervention to prevent a single suicide attempt. High false-positive rates have been a persistent challenge in screening efforts 6 that have not been overcome by machine learning prediction models. 7 Even in a system willing to invest those resources, the model's sensitivity was only approximately 41%, indicating that nearly 60% of suicide attempts would be missed.…”
mentioning
confidence: 99%